2016
DOI: 10.1159/000443058
|View full text |Cite
|
Sign up to set email alerts
|

Association Studies Between XRCC1, XRCC2, XRCC3 Polymorphisms and Differentiated Thyroid Carcinoma

Abstract: Background/Aims: DNA HRR pathway and BER pathway play vital roles in differentiated thyroid cancer (DTC) development, thus we supposed that polymorphisms of XRCC1, XRCC2, XRCC3 DNA repair genes are associated with thyroid cancer risk and progression. Methods: We searched the NCBI database for relevant literatures to determine eight SNPs to be included in our study (XRCC1: rs25487, rs25489, rs1799782; XRCC2: rs3218536; XRCC3: rs1799794, rs56377012, rs1799796, rs861539). Results: SNP of rs25487 was linked with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…The present combined genotype frequency and their significance in thyroid carcinogenesis may show the synergistic effect of the selected polymorphisms on the said disease. So for only a few studies have been conducted regarding the combined genotypes of XRCC3 SNPs and their involvement in cancer, [59, 20] but the results are not comparable because they genotyped different SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The present combined genotype frequency and their significance in thyroid carcinogenesis may show the synergistic effect of the selected polymorphisms on the said disease. So for only a few studies have been conducted regarding the combined genotypes of XRCC3 SNPs and their involvement in cancer, [59, 20] but the results are not comparable because they genotyped different SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Arg194Trp and Arg399Gln polymorphisms are among the most extensively studied SNPs in the XRCC1 gene (25,29,30,3335,37,46,51, 5355,5963). These two SNPs have been shown to alter the functional activity of the resulting protein in vitro and to interfere with cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have identified base excision repair (BER) genes polymorphisms associated with breast and thyroid cancer risk (3335) among other malignancies, and a nucleotide excision repair gene polymorphism displayed strong association with leukaemic transformation and development of non-myeloid malignancies in patients with ET and PV (24). …”
Section: Introductionmentioning
confidence: 99%
“…Recently, two studies have reported associations of between XRCC1 and XRCC3 gene polymorphisms and risk of TC [11,12], but they concluded inconsistent results. In addition, increasing evidence suggests that combination of both genetic and environmental risk determinants contribute to the development and progression of PTC.…”
Section: Introductionmentioning
confidence: 99%